Reinterpretasi Makna Jihad Dan Teroris - Musda Asmara (AL-ISTINBATH : Jurnal Hukum Islam, 2016)
This paper aims to find a very clear distinction between jihad and terrorism. The concept of jihad is often regarded as the source of the proliferation of terrorism because of misunderstanding in understanding religion. The very hard thought of religion or radicalism with certain genes can has increasingly strong role for the growth of extremism, terrorism which finally will act of terror on the pretext of jihad fi sabilillah. The situation and the opportunity was used by the enemy to continue claimed that “Islam is terrorism”. The data presented in this paper is sourced from some literatures. The results of this paper, that jihad is the real struggle whether with the soul, materials, verbal acts and thoughts in order to up hold the religion and Islamic values peacefully. Instead of terrorists is an act of terrorizing, threatening, frightening the masses with certain motives and goals.